Investigating Impacts of Incorporating an Adjuvant Mind–Body Intervention Method Into Treatment as Usual at a Community-Based Substance Abuse Treatment Facility: A Pilot Randomized Controlled Study. (18th February 2015) - Nakamura, Yoshio; Lipschitz, David L.; Kanarowski, Elizabeth; McCormick, Theresa; Sutherland, Debbie; Melow-Murchie, Melinda
Treatment of substance use/misuse (SUM) continues to pose a difficult challenge. This exploratory pilot study evaluated whether a novel mind–body intervention program called "Mind–Body Bridging" (MBB) could be an effective short-term adjuvant intervention for managing SUM and coexisting symptoms in women undergoing residential and outpatient substance use treatment in a community setting. Thirty-eight women attending a local substance abuse (SA) facility were recruited and randomly assigned to either (a) treatment as usual (TAU) or (b) MBB and TAU. The MBB program consisted of 20 sessions and lasted for 10 weeks. Participants were asked to complete a set of self-report questionnaires designed to assess drug/alcohol cravings, impact of past trauma, depression, sleep disturbance, mindfulness, self-compassion, and well-being. They completed the questionnaires at three time points: preintervention, midintervention (after the fifth week), and postintervention. MBB + TAU significantly reduced drug/alcohol cravings, trauma-related thinking, and disturbed sleep in comparison with TAU. Furthermore, MBB + TAU significantly increased mindfulness, self-compassion, and well-being in comparison with TAU. MBB for SUM appears promising as a complementary adjuvant intervention, warranting future larger scale randomized controlled trials of MBB for SUM populations. SUM is a difficult condition to treat and manage clinically, especially given the multiple comorbid conditions that frequently affect those with SUM. In the search to develop effective adjuvant interventions for SUM, the present pilot study suggested that adding MBB to standard SUM treatment in community-based settings could enhance therapeutic efficacy and quality of care.